INVESTIGATING THE RELATIONSHIP OF EMOTIONAL INTELLIGENCE TOWARDS ACADEMIC ACHIEVEMENT AMONG TESL TEACHER TRAINEES IN MALAYSIA INSTITUTE OF TEACHER EDUCATION - Abd. Aziz, Azlinda (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract Teacher trainees need to be well equipped to face the 21st Century education. Emotional characteristics of teachers emerged to be significantly important as their intellectual development in order to overcome the future obstacles and challenges in the proffesion.Emotional intelligence is the ability to manage emotions. It is discussed on four dimensions namely self-emotion appraisal, othersâ emotion appraisal, regulation of emotion and use of emotion.This study is conducted to investigate the relationship of emotional intelligence dimensionstowards academic achievement among TESL (Teaching English as a Second Language) Teacher Trainees. Each of the 500 participants completed Wong and Law Emotional Intelligence Scale (WLEIS), a self-report scale based on four- dimensional definition of emotional intelligence. Data were analysed through descriptive statistics using SPSS and multivariate analysis using Structural Equation Model (SEM) via Analysis of Moment Structure (AMOS) software. The results showed that there is a significant relationship between two emotional intelligence dimensions, namely use of emotion and regulation of emotion, towards academic achievement. Findings imply that the development of emotional skills should be strengthen and enhanced in planning the curriculum for teacher trainees. This is important so that the future generations of teachers will be well balanced in term of cognitive and emotional domains.Keywords: emotional intelligence, academic achievement, teacher trainees, Teaching English as Second Language